Platform workers not by chance: Exploring the digital labour markets in Italy with machine learning and explainable AI - Clara Punzi; Valeria Cirillo; Dario Guarascio; Roberto Pellungrini; Fosca Giannotti (PLoS ONE, 2026)
Digital labour platforms are reshaping the world of work across a wide range of sectors, offering greater flexibility and accessibility than traditional labour markets. However, existing research suggests that platform work is often associated with low-quality working conditions and may exacerbate inequalities. This study examines the economic and social dimensions of digital platform labour in Italy—a country characterised by labour market fragmentation and the widespread use of non-standard employment—using official survey data collected in 2018 and 2021. Applying advanced machine learning (ML) and explainable artificial intelligence (XAI) techniques, the analysis explores the demographic, occupational, and economic factors that predict participation in platform work and drive segmentation within the platform workforce. The findings reveal that platform work in Italy is a heterogeneous and stratified phenomenon, deeply embedded in longstanding labour market fragmentation and regional disparities. Economic vulnerability is concentrated not among the youngest workers, as often suggested in the literature, but among older or more established individuals facing job instability, underemployment, or declining income from traditional occupations. Moreover, the analysis reveals that platform work is associated with structural vulnerabilities typical of non-standard employment, including unstable contracts, gender inequalities, and economic insecurity, and it primarily functions as a compensatory mechanism to supplement insufficient earnings from precarious jobs. Among jobseekers, engagement with platforms is more likely among younger individuals experiencing moderate—rather than severe—financial strain, suggesting that platform work is not generally perceived as a last-resort strategy but rather as a temporary or adaptive response to limited labour market opportunities. The COVID-19 pandemic further intensified these dynamics, acting as a catalyst for workers experiencing economic and social stress. During this period, platform work expanded as a fallback option for the unemployed, providing an informal buffer amid declining employment opportunities and persistent income insecurity.